Capacity interaction in brick masonry under simultaneous in-plane and out-of-plane loads - Najafgholipour, M. A. (2013)
A considerable number of numerical and experimental studies, carried out to-date to investigate the behaviour of masonry walls under seismic loading, have considered the in-plane or the out-of-plane response of the wall separately without due consideration for any possible interaction between the two responses. In this paper, the results of a series of tests with different levels of simultaneous in-plane shear and out-of-plane bending actions on small brick walls are presented. The tests results indicate noticeable interaction between the in-plane shear and out-of-plane bending strengths of brick walls. Test results are also used to validate representing numerical models of wall panels. The combined in-plane/out-of-plane capacity interaction in full-scale walls having different aspect ratios is then investigated using these numerical models. It is found that the wall aspect ratio highly influences the interaction level, which must be considered in masonry design.